2017
DOI: 10.5812/semj.13092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of Combination of Acetaminophen, Ibuprofen and Caffeine on Pain Relief and Analgesic Use After Impacted Lower Third Molar Surgery

Abstract: Objectives: Relieving a very painful procedure such as impacted lower third molar surgery by combining analgesics into a single product using their synergistic effects is favorable. We designed a prospective, randomized, double-blind clinical trial to study the beneficial effect of the combination of acetaminophen, ibuprofen, and caffeine on reducing the severity of postoperative pain after impacted lower third molars surgery. Methods:This was a double-blinded clinical trial on 108 patients scheduled for impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A systematic review by Cetira Filho et al [40] demonstrated that the intensity of pain after the removal of these teeth is often moderate to severe, which may require more effective medications or a multimodal strategy based on the combination of different drugs [48]. The study by Asadi et al [49] showed that combined NSAIDs (acetaminophen 600 mg, ibuprofen 400 mg, and caffeine 15 mg) reduced pain intensity in the rst 8 hours postoperatively. Cigerim & Eroglu [44] also demonstrated that combined medications (NSAID + opioid) had better clinical outcomes regarding pain in the rst 24 hours postoperatively compared to the isolated use of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Cetira Filho et al [40] demonstrated that the intensity of pain after the removal of these teeth is often moderate to severe, which may require more effective medications or a multimodal strategy based on the combination of different drugs [48]. The study by Asadi et al [49] showed that combined NSAIDs (acetaminophen 600 mg, ibuprofen 400 mg, and caffeine 15 mg) reduced pain intensity in the rst 8 hours postoperatively. Cigerim & Eroglu [44] also demonstrated that combined medications (NSAID + opioid) had better clinical outcomes regarding pain in the rst 24 hours postoperatively compared to the isolated use of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%